Ethnopharmacology of The Tengger Tribe Society: Inventory Study of The Use of Medicinal Plants - Hadi Prayitno; . Ari P; Erwin Nur Rif’ah; Dewi Rokhmah (Journal of Global Pharma Technology, 2020)
The Tenggerese community is a community that inhabits the area commonly called